Apedilum griseistriatum comb. nov., placement of Chironomus (Polypedilum) griseistriatum (Diptera, Chironomidae) - Donato, Mariano Humberto (2015)
The study of the type material of Chironomus (Polypedilum) griseistriatum Edwards, 1931 described from Patagonia lead us to formally transfer the species to Apedilum Townes, 1945 as a new combination, and a reared specimen allows us to describe its pupa. Based on several larvae belonging to Apedilum collected in the proximity of the localities in which the adults and pupae were found, we tentatively describe the larval stage. Subfossil larval head capsules of the same species were found in Laguna Stibnite at 46°S in Chile dated to about 2,500 years ago and in Puerto Blest, Lago Nahuel Huapi at 41°S in Argentina dated about 2,000 years ago. We discuss the habitat of the species based on both modern and subfossil material. Identifcation keys to male adult, pupae and fourth instar larvae are also provided.